Cultural differences in product design between the UK and China - Tang, Fangyan (2016)
Design is one of the significant intellectual activities of human beings and is therefore inevitably influenced by culture, which as Hofstede describes, influences ‘all aspects of human life’. Product design, which emerged in the middle of the last century and is developing under the background of globalization, is a relatively young domain in the design area and also unavoidably a topic of interest in the field of culture study. This thesis brings forth a perspective on the need for an examination of product design in a cross-cultural context. Product design in this research was decomposed into two main components: the design outcome and design process. Two empirical studies were conducted to investigate the cultural differences from the perspective of design outcome. The technique of repertory grid analysis, applied in interviews with participants from the UK and China, found distinctive attributes of designs created by student designers. The designs from the UK students tended to have rounded shapes, simple structures, fewer functions and less creativity; whereas the designs from the Chinese student designers tended to have squarer shapes, more complex structures, more functions and greater creativity. Notable differences were also found in the criteria of design evaluation: people from the UK and China had different emphases on aesthetics, ergonomics and creativity. The differences in design evaluation were validated with a larger sample size using an online survey. Differences in design process were also revealed by two empirical studies that investigated the design activities of designers from the two cultures. A study using a post-hoc reflective method was conducted to analyse submissions from design students, supplemented with an ethnographic observation of daily design activities in a studio. Differences were found in the patterns of design process as well as in the design cognitions revealed through the design representations. UK students were found to sketch more and used sketching as a means of recording, presenting and generating ideas, whereas Chinese students tended to sketch less and used sketching more as a tool for recording and presenting ideas. Chinese students also showed an obvious tendency towards considering a design task in a relational-contextual way, i.e. they tended to consider the relationships between different themes. The differences were confirmed in a protocol study with design practitioners, in which experienced designers were asked to design a condiment stand and subsequently explain their process. UK designers were found to be design-attributes oriented, whereas Chinese designers were more use-environment oriented. Also, compared to their UK counterparts, the design processes of the Chinese designers tended to be more simplified. The differences found in the perspectives of design process and design outcome can be attributed to cultural differences addressed by cultural models such as those from Hofstede. The literature on the cognitive differences between the UK and China also suggested deep-rooted reasons for the relevant differences, such as the analytic cognitive style of UK people and the holistic style of Chinese people, which make them have different focus on interpreting things. The findings of this research offer valuable information in guiding product design activities taking place in the UK / China or any other similar cultures in two ways: 1) the differences in design evaluation criteria offer valuable references to design practice in the relevant markets, i.e. different emphases on the aspects of aesthetics, ergonomics and creativity should be taken when designing for the relevant market; 2) the differences found in design cognition and patterns in design process also provide valuable information: a) for design education, it suggests that Chinese design students should be encouraged to use sketching as a tool for thinking and generating ideas and also to present more of their cognitive process, so as to develop more structured thinking processes to facilitate design; b) for collaborative design practice in a multi-cultural environment, which is typical of today’s product industry, it suggests an integration of different views of designers during early design stage to make more thorough investigation of the design problem, and also a more flexible management in the idea developing stage to fit with the different cognitive styles of the designers.